2008
DOI: 10.1111/j.1753-4887.2007.00001.x
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhoods and obesity

Abstract: This review critically summarizes the literature on neighborhood determinants of obesity and proposes a conceptual framework to guide future inquiry. Thirty-seven studies met all inclusion criteria and revealed that the influence of neighborhood-level factors appears mixed. Neighborhood-level measures of economic resources were associated with obesity in 15 studies, while the associations between neighborhood income inequality and racial composition with obesity were mixed. Availability of healthy versus unhea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
383
3
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 451 publications
(426 citation statements)
references
References 128 publications
15
383
3
10
Order By: Relevance
“…8,9 Behavioral risk factors for diabetes include poor quality diet, inadequate exercise, limited medication adherence, and depression, 10,11 all of which are common among poor, medically uninsured patients. 12 …”
Section: Introductionmentioning
confidence: 99%
“…8,9 Behavioral risk factors for diabetes include poor quality diet, inadequate exercise, limited medication adherence, and depression, 10,11 all of which are common among poor, medically uninsured patients. 12 …”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have identified the influence that space and place have on dietary intake, both internationally (9)(10)(11) and in the UK (12)(13)(14) . However, research has focused largely on one of two factors: (i) the effects of neighbourhood-level deprivation (15)(16)(17)(18) ; and (ii) the role that distance or access to food outlets plays in diet (19)(20)(21)(22)(23)(24) .…”
mentioning
confidence: 99%
“…The patient's home neighbourhood will be used as a surrogate for patient characteristics, because previous literature shows an association between home neighbourhood and cardiac risk factors, unhealthy behaviours, and overall health. [33][34][35][36][37][38][39][40][41][42][43][44][45] The neighbourhood factors of the arrest location (i.e., the pickup address) will be used to study the effects on bystander CPR, because the emergency response (i.e., bystanders and EMS/paramedics) is contingent on the arrest location. [10][11][12][13][46][47][48] A patient's home address is recorded as mailing address with street name, street number, and postal code, whereas the pickup address is recorded as a mailing address, with latitude and longitude coordinates and a Universal Transverse Mercator (UTM) value.…”
Section: Geocodingmentioning
confidence: 99%